Two domains of anosognosia in Alzheimer's disease. Issue 5 (November 1996) - Starkstein, S E; Sabe, L; Chemerinski, E; Jason, L; Leiguarda, R
Abstract : OBJECTIVE: To examine the presence of different dimensions of unawareness in patients with probable Alzheimer's disease. METHODS: A consecutive series of 170 patients with probable Alzheimer's disease were assessed with the anosognosia questionnaire-dementia (AQ-D) which includes items related to cognitive deficits and behavioural problems. RESULTS: A factor analysis of the AQ-D produced two factors: a "cognitive unawareness" factor, which loaded on items of memory, spatial and temporal orientation, calculation, abstract reasoning, and praxis, and a "behavioural unawareness" factor which loaded on items of irritability, selfishness, inappropriate emotional display, and instinctive disinhibition. A stepwise forward regression analysis showed significant correlations between the cognitive unawareness factor and more severe cognitive deficits, delusions, and apathy, but less depression. On the other hand, the behavioural unawareness factor correlated significantly with higher mania and pathological laughing scores. Whereas the cognitive unawareness factor showed a significant correlation with cognitive tests assessing verbal comprehension and long term memory, and was significantly associated with a longer duration of illness, no significant correlations were found between the behavioural unawareness factor and the neuropsychological tasks. CONCLUSION: Unawareness of cognitive deficits and unawareness of behavioural problems may constitute independent phenomena in Alzheimer's disease. Whereas unawareness of cognitive deficits is related to the severity of intellectual impairment and the presence of delusional apathetic mood, unawareness of behavioural problems may be part of a disinhibition syndrome.